Investment Literacy and Inclusion among Online Community in Indonesia - Putro, Lucky Wahyu Pratomo; Nainggolan, Yunieta Anny (Journal of Business and Management, 2016)
Abstract. In the globalization era, internet is essential tools that provide us so many conveniences to ease our daily lives. Including in the financial sector. Internet helps increasing the financial understanding of people. Financial literacy and inclusion is one of the important things in determining the economic situation of a country. Financial literacy and inclusion could be achieved by financial education. The data collected from the World Bank shows that Financial Inclusion in Indonesia only reach 30% of total Indonesian adults. One of the easiest way to improve Indonesian economy is by implementing financial education specialized in investment, such as Mutual Fund, Stock, and Bond. This study is to determine the level of Investment literacy and inclusion among Indonesia largest online community such us detik, kaskus, and kompasiana. The data collected from the questionnaire that will be spread on the internet to the online community. The questionnaire is based on the research that conducted by Ronald P. Volpe, World Bank, and Otoritas Jasa Keuangan. The result suggested that there is still low Investment literacy and Inclusion in Indonesia online community, and still needed to be improved significantly.Keywords: Investment Literacy; Investment Inclusion; Online community